The Main Trends in the International Effort to Strengthen Global Liquidity after the Financial Crisis of 2008/2009 (Czech Journal of International Relations, 2011)
Significant international attention has been directed to the most pressingproblem of the financial crisis of 2008/2009 – global liquidity shortages. Theuse of adequate foreign exchange reserves during the crisis helpedalleviate pressures. However, this was only partially effective in a number ofimportant cases. Some countries also needed to rely on external officialfinancing. The aim of this article is to compare and analyse the mainsources of official global liquidity - foreign exchange reserves, bilateralswap lines of central banks, regional financial arrangements and IMFresources. To reach effective outcomes in relation to the accumulation of FXreserves and a strengthening of the global financial safety nets, effectiveinternational coordination will be necessary.
Keywords: Global financial safety nets; bilateral swap lines; the IMF lending; foreign exchange reserves; regional financial arrangements; G-20; financial crisis